2015
DOI: 10.1111/imr.12320
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the NKG2D ligand gene family

Abstract: NKG2D ligands (NKG2DLs) are a group of stress-inducible major histocompatibility complex (MHC) class I-like molecules that act as a danger signal alerting the immune system to the presence of abnormal cells. In mammals, two families of NKG2DL genes have been identified: the MIC gene family encoded in the MHC region and the ULBP gene family encoded outside the MHC region in most species. Some mammals have a third family of NKG2DL-like class I genes which we named MILL (MHC class I-like located near the leukocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 116 publications
(152 reference statements)
0
13
0
Order By: Relevance
“…Importantly, the activity of NK cells is regulated by the balance of inhibitory and activating signals received via inhibitory and activating NK receptors ( 37 ). One of the most important activating NK receptor is NKG2D that interacts with a group of stress-inducible ligands including the RAE-1 and H60 families and MULT-1 in the mouse ( 36 , 57 ). We and others have shown that murine ESCs are among the few cell types that constitutively express NKG2D ligands ( 31 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the activity of NK cells is regulated by the balance of inhibitory and activating signals received via inhibitory and activating NK receptors ( 37 ). One of the most important activating NK receptor is NKG2D that interacts with a group of stress-inducible ligands including the RAE-1 and H60 families and MULT-1 in the mouse ( 36 , 57 ). We and others have shown that murine ESCs are among the few cell types that constitutively express NKG2D ligands ( 31 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…NKG2D is a prominent activating NK cell receptor that can also be a co‐receptor for T cells. NKG2D is very conserved and also distinguished by the variety and polymorphism of its MHC class I‐like ligands . These ligands are not present on the surface of healthy cells, but expression is induced by the stress of infection or malignant transformation.…”
Section: Conserved and Variable Nk Cell Receptorsmentioning
confidence: 99%
“…There are MICA homologs in the genomes of almost all mammals studied except rodents (Kasahara & Sutoh, ). We identified homologs of both the upstream and standard transcripts for pigs and cows (Fig EV1C) and alignment with the corresponding genomes revealed conservation of the tandem promoter gene structure and local sequence around the upstream promoter in these species and humans (Fig EV1C and D).…”
Section: Resultsmentioning
confidence: 99%
“…Engagement of NKG2D on NK cells by MICA expressed on target cells promotes cytokine release and killing of the target cells and is implicated in cancer immunity, antiviral immunity and autoimmunity (Bauer et al , ; Ullrich et al , ; Lanier, ). Homologs of the MICA gene are present in all mammals studied, except rodents (Kasahara & Sutoh, ). The MICA gene is highly polymorphic, with over 80 coding alleles known to date (Robinson et al , ).…”
Section: Introductionmentioning
confidence: 99%